Variation in information obtained from interpretation of ground penetrating radar (GPR) pavement investigation data - Robert D. Evans; Matthew Frost; Neil Dixon; Martyn Stonecliffe-Jones (2007)
Ground penetrating radar (GPR) data can be used to provide useful information about pavement structures. However, some limitations exist relating to GPR technology, and various limitations and uncertainties can exist in the reported information depending on the investigation methodology and the data analysis procedure used. The combination of all these factors results in a significant potential for uncertainty or variations in the analyzed data, and therefore consideration is required if the optimum amount of information from a GPR investigation is to be obtained. This paper discusses the possible errors and uncertainties that can arise from GPR investigations, and GPR pavement data is used to illustrate issues that can arise during data analysis and interpretation. Ways of minimizing and managing variations and uncertainties are discussed, and the use of appropriate data collection and analysis procedures are highlighted, so that the use of information from GPR can be optimized.